2020
DOI: 10.35808/ersj/1902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 in the Financial Statements of Selected Companies Listed in Warsaw Stock Exchange

Abstract: Purpose: The objective of this article is to evaluate the quality of the presented content concerning the impact of the COVID-19 pandemic on continuing activities of selected companies listed in Warsaw Stock Exchange. Design/Methodology/Approach: In the first part we applied critical review of subject literature and the monographic method. In the second part, the content analysis method was used, and the basic source material were the financial statements-annual for 2019 and interim for 2020. Findings: Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The study examined the implications of the recent pandemic for corporate governance, directors' remuneration and the sustainability performance of companies. The central findings revealed that the COVID19 pandemic negatively impacted the selected companies while it benefiting some companies belonging to the health, telecommunications and food industries as revealed by the findings which are similar to those of Honko, et al [51] and Hategan, et al [52]. For instance, the results revealed that the estimated coefficient of COVID-19 related expenses is negative but significant in all estimated models.…”
Section: Study Implicationsupporting
confidence: 71%
“…The study examined the implications of the recent pandemic for corporate governance, directors' remuneration and the sustainability performance of companies. The central findings revealed that the COVID19 pandemic negatively impacted the selected companies while it benefiting some companies belonging to the health, telecommunications and food industries as revealed by the findings which are similar to those of Honko, et al [51] and Hategan, et al [52]. For instance, the results revealed that the estimated coefficient of COVID-19 related expenses is negative but significant in all estimated models.…”
Section: Study Implicationsupporting
confidence: 71%
“…The outbreak of the SARS-CoV-2 pandemic changed every aspect of our lives in a very short time (Flaga-Gieruszynska, 2020;Witczynska, 2020;Grima et al, 2020;Khan et al, 2020). It has had a huge impact on the entire world economy (Honko et al, 2020), and thus also on the labour markets (Kozicki and Gornikiewicz, 2020). These specific conditions certainly influenced young people's visions of the future and their expectations.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting study was conducted by Honko et al [66]. The authors found that companies listed on the Warsaw Stock Exchange did not indicate the risk caused by a pandemic in their financial statements.…”
Section: Discussionmentioning
confidence: 99%